EXPLORING THE MOTHERS UTILIZATION OF FOOD ITEMS FOR INFANTCOMPLEMENTARY FEEDING WITH CHILDREN (6-23) MONTHS IN ENUGU STATENIGERIA: A FOCUS GROUP DISCUSSION (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
The focus group discussion highlights a clear preference for yellow maize 66.7%, primarily due to its familiarity among women and its appealing color. The yellow pigmentation, associated with βcarotene—a precursor of vitamin A—is believed to contribute to its high acceptability. β-carotene, abundant in yellow-colored plant foods, supports vision, skin health, cancer prevention, and combats vitamin A deficiency. Traditional food processing techniques such as soaking, fermenting, sun drying, roasting, and milling were commonly employed by women in the study area. These methods enhance the digestibility, shelf life, and nutritional quality of complementary foods, especially when combined with amino acid-rich ingredients. Notably, fermentation introduces probiotics that benefits gastrointestinal health. Soaking roasting and milling increases shelf- life of CF. However, the study also observed that a significant number of women (53.3%) introduced complementary foods before the recommended six-months period, which  contributes to adverse health outcome such as retarded growth, atopic diseases, and increased risk of type 1 diabetes. The findings underscore the need for nutritional education and promotion of appropriate complementary feeding practices to ensure optimal infant development.